Glaciological Data Collected by the 29th Japanese Antarctic Research Expedition in 1988-1989 - WATANABE, Okitsugu; FURUKAWA, Teruo; FUJITA, Shuji (National Institute of Polar Research, 1990)
P(論文) departmental bulletin paper